Meta-Analysis the Effectiveness of Speech Therapy on Phonation Improvement in People Diagnosed with Parkinsons Disease - Anitasari Kartika Putri; Hanung Prasetya; Bhisma Murti (Indonesian Journal of Medicine, 2023)
Background:  Parkinson's disease (PD) is a complex, progressive neurodegenerative disease characterized by tremor, rigidity, slow movement, and postural instability. Phonation disturbances are the most frequently observed speech characteristics in PD patients. The purpose of this study was to estimate the effectiveness of speech therapy interventions for phonation improvement in people with a diagnosis of Parkinson's disease.Subjects and Method:  This study is a meta-analysis of a number of Randomized Controlled Trial study designs. The articles used in this study were obtained from several databases including PubMed, Google Scholar, and Springer Link. The article search was carried out by considering the eligibility criteria defined using the PICO model. The population in the study were people with a diagnosis of Parkinson's disease with intervention in the form of speech therapy intervention, comparison, namely no speech therapy intervention, outcome in the form of phonation. The keywords to search for articles are as follows: “Intervention Speech Therapy” OR “Speech Therapy” OR “Phonation” OR “Voice” OR “Parkinson's Disease” AND “Randomized Controlled Trial” OR “RCT”. The articles included in this study are full-text articles with a Randomized Controlled Trial (RCT) study design. Articles are collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results:  A total of 7 articles were reviewed in this study from the United States, North America, and Austria. The total sample size in this study was 213 subjects. A meta-analysis showed that speech therapy was effective for improving phonation in people with a diagnosis of Parkinson's disease (SMD = 2.52; 95% CI = 1.79 to 3.24; p<0.001).Conclusion:  Speech therapy is effective for improving phonation in people with a diagnosis of Parkinson's disease.Keywords:  speech therapy, phonation, voice, parkinson disease.Correspondence: Anitasari Kartika Putri. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: anitaaakartika@gmail.com Mobile: 0857-2777-7217Indonesian Journal of Medicine (2023), 08(03): 277-285https://doi.org/10.26911/theijmed.2023.08.03.05